Transforming TPA Governance Through Total Quality Management to Enhance Institutional Competitiveness - Syarifah Fatimah Zahara; Risfa Tri Ulfa (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This study examines the implementation of Total Quality Management (TQM) in transforming the governance of Taman Pendidikan Al-Qur'an (TPA) to enhance institutional competitiveness. The study is important because the application of TQM in non-formal Islamic educational institutions remains underexplored despite increasing demands for professional and sustainable educational management. A qualitative case study design was employed involving seven purposively selected informants, including the head of the institution, administrative staff, teachers, and parents. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model with triangulation and member checking to ensure trustworthiness. The findings indicate that TQM implementation strengthened governance through systematic quality planning, standardized service delivery, human resource development, digital-based administration, and continuous improvement. These practices improved service quality, strengthened public trust, expanded student enrollment, and enhanced institutional competitiveness. The study concludes that integrating TQM principles with digital governance provides an effective strategy for developing adaptive, professional, and sustainable management in Qur'anic education institutions.